2020
DOI: 10.1111/jgh.14997
|View full text |Cite
|
Sign up to set email alerts
|

Terminal ileum intubation is not associated with colonoscopy quality measures

Abstract: Background and Aim: Intubation of the terminal ileum (TI) demonstrates a complete colonoscopy, but its clinical value during screening exams is unknown. We aimed to determine whether TI intubation during screening colonoscopy is associated with colonoscopy quality measures or identifies subclinical pathology. Methods: We performed a retrospective cohort study examining average-risk screening colonoscopies performed at an academic health system between July 2016 and October 2017. Data were extracted from an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Also, interestingly, short cecal insertion time was predictive of ileal intubation in our cohort. Lieman et al reached a similar conclusion in their retrospective study that showed prolonged cecal insertion time was associated with a lower likelihood of ileal intubation (median and interquartile range: 6 [ 4 , 10 ] vs. 5 [ 4 , 8 ]; p<0.0001) [ 21 ].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Also, interestingly, short cecal insertion time was predictive of ileal intubation in our cohort. Lieman et al reached a similar conclusion in their retrospective study that showed prolonged cecal insertion time was associated with a lower likelihood of ileal intubation (median and interquartile range: 6 [ 4 , 10 ] vs. 5 [ 4 , 8 ]; p<0.0001) [ 21 ].…”
Section: Discussionmentioning
confidence: 73%
“…Our study reported a higher ileal intubation rate among younger individuals undergoing screening colonoscopy. Existing studies report conflicting results regarding the association between the age of the patients and the likelihood of ileal intubation [ 2 , 14 , 21 , 22 ]. It is not clear why successful ileal intubation is more achievable in younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting data regarding the association between age and likelihood of successful TII [ 2 , 19 , 25 ]. For example, lower TII rates among elderly patients have been previously observed in studies that included patients undergoing colonoscopy for non-screening indications [ 2 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lower TII rates among elderly patients have been previously observed in studies that included patients undergoing colonoscopy for non-screening indications [ 2 , 19 ]. On the other hand, 2 large retrospective studies concluded that age was not associated with a higher likelihood of TII [ 25 , 26 ]. Our study found that younger patients were more likely to have successful TII.…”
Section: Discussionmentioning
confidence: 99%